An Account of the General and Forest Vegetation of Patiala District (punjab) - Sharma, M. (Indian Forester, 1981)
The paper gives a detailed description of the general and forest vegetation of Patials District and is a step forward for compiling the ’Flora’ of the reorganized Punjab.